The Complex Sentences in Kurmanji - Mikail Bülbül (گۆڤارا زانستێن مرۆڤایەتی یا زانكۆیا زاخۆ, 2019)
This study deals with the analysis and classification of complex sentences in terms of both syntactical and semantical features. There are many kinds of the complex sentences and they frequently consist of a main clause and a subordinate clause or a complement clause. Especially the complement clauses which are at the object position of the the main clauses are used widely and vary widely both syntactically and semantically. In addition the complex sentences can be constituted by the relative clauses which modify a constituent such as a subject, object or an indirect object in a clause; the modal, manipulative verbs’s clauses and aspective verbs. However, there are complex sentences which are separated and include two or more different types of clauses mentioned above.